Dampak Layanan Transportasi Online Terhadap Kesejahteraan Perekonomian Masyarakat Kota Mojokerto Melalui Kesempatan Kerja - Khasbulloh Huda; Zenita Afifah Fitriyani; Rachmad Sholeh; Mohammad Johan Effendi (STKIP PGRI SITUBONDO, 2021)
Abstract: This study aims to determine the impact of online transportation services on the economic welfare of the people of Mojokerto city through job opportunities. This research was conducted with a quantitative approach using a survey method and using random sampling data collection method. While the measurement uses a Likert scale. The data collection method used a questionnaire. The data analysis method in this study uses PLS (Partial Least Square) with the smartPLS 3.0 program. Online transportation services have a direct influence on job opportunities for the people of the city of Mojokerto with a T statistic of 9.007 (P value = 0.000). Online transportation services have a direct influence on the economic welfare of the people of Mojokerto city with a T statistic of 10,746 (P value = 0.000). Job opportunities have an influence on the economic welfare of the people of Mojokerto city with a T statistic of 11.471 (P value = 0.000). Online transportation services have an influence on the economic welfare of the people of Mojokerto city through job opportunities with a T statistic of 7.193 (P value = 0.000). Keywords: Online Transportation Services, Community Economic Welfare, Job Opportunities, Mojokerto City.